In vitro Cytotoxicity of Nitroxyl Radicals with Respect to Tumor and Diploid Human Cells and Estimation of Their Antiviral Activity - I. A. Kirilyuk; V. A. Svyatchenko; D. A. Morozov; E. I. Kazachinskaya; N. N. Kiselev; S. M. Bakunova; M. A. Voinov; V. B. Loktev; I. A. Grigoryev (Антибиотики и Химиотерапия, 2020)
Thirty nine water soluble nitroxyl radicals of various classes, belonging to piperidine, pyrrolidine and imidazolidine series were synthesized. Twenty seven of them were cytotoxic in vitro with respect to the tumor cell culture A431. The CC50 of the most active nitroxyl radicals with respect to cells SW480 and A431 was within 0.16-2.5 mM at the selectivity index of 3.91-7.81 in relation to cytotoxicity of the compounds for the cells of the normal L68 phenotype and tumor cells. The tests on the antiviral activity showed that 16 out of 22 nitroxyl radicals had antiviral activity in Vero cell culture with respect to the West Nile virus and Herpes simplex virus of type II respectively. The EC50 ranged within 0.09-3.45 mM. Some of the nitroxyl radicals had only antiviral activity, but a number of the compounds had both cytotoxic properties and antiviral activity.